Insights into physicochemical properties, stability in various aqueous media, and antibacterial activity of gallium-containing amorphous calcium phosphates - Renats Vasiljevs; Marika Sceglova; Liga Stipniece; Janis Locs (Scientific Reports)
Abstract Amorphous calcium phosphate (ACP) is a metastable phase that spontaneously crystallizes upon contact with aqueous media. Furthermore, modification of ACP with metal ions to confer specific biological functions may affect its stability. Crystallization of ACP is accompanied by physicochemical changes, which affect its biological properties. In this study, ACP powders with Ga content up to 2.2 ± 0.2 wt% were synthesized using a modified wet precipitation method. The synthesized powders’ phase composition, functional groups, and morphology were analyzed. Overall, adding up to 2.2 ± 0.2 wt% of Ga had a negligible effect on the ACP physicochemical properties. The Ga-containing ACP (GaACP) stability was evaluated in deionized H2O, phosphate buffer solution (PBS), Dulbecco’s modified Eagle’s medium (DMEM), and tryptone soya broth (TSB). The Ga content and the composition of the incubation media affected the stability of the GaACP powders. The most stable GaACP powders were in deionized H2O (reached 90 min), but the least stable were in PBS. Moreover, increasing the Ga content in ACP improved the powder stability in DMEM and TSB. The antibacterial activity of the synthesized powders was assessed against Pseudomonas aeruginosa and Staphylococcus aureus. It was confirmed that incorporating Ga into ACP may confer inhibitory potential on bacterial growth.